2010
DOI: 10.1002/pmic.200900586
|View full text |Cite
|
Sign up to set email alerts
|

Increased interaction between DJ‐1 and the Mi‐2/ nucleosome remodelling and deacetylase complex during cellular stress

Abstract: DJ-1 was originally identified to be an oncogenic product, but has later been shown to be highly multifunctional. DJ-1 plays a role in oxidative stress response and transcriptional regulation, and loss of its function leads to an early onset of Parkinsonism. To further understand the mechanisms behind DJ-1's role in cell survival and death, we investigated alternations in endogenous DJ-1 protein-protein interaction in apoptotic cells exposed to the phosphatase inhibitor okadaic acid. By combining cellular stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Lower DJ-1 levels were also observed in lung tissue obtained from patients with chronic obstructive pulmonary disease compared with that from control smokers (11). Moreover, it was previously reported that DJ-1 can protect cells from cell death in vitro (41). In our next approach, we wanted to determine the role of Nrf2 in ATII cell injury by CS.…”
Section: Discussionmentioning
confidence: 96%
“…Lower DJ-1 levels were also observed in lung tissue obtained from patients with chronic obstructive pulmonary disease compared with that from control smokers (11). Moreover, it was previously reported that DJ-1 can protect cells from cell death in vitro (41). In our next approach, we wanted to determine the role of Nrf2 in ATII cell injury by CS.…”
Section: Discussionmentioning
confidence: 96%
“…Deacetylation of p53 is mediated by an HDAC1-containing complex that includes Mi-2/ nucleosome remodeling and deacetylase (NuRD) complex [71]. Opsahl et al [72] reported that DJ-1 is a core component of the NuRD complex. They suggested that downregulation of DJ-1 facilitates p53-dependent cell death in response to apoptotic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Even though cytoskeletal proteins do not directly interact with lipid membranes, they interact with proteins that associate with rafts of the inner leaflet of the plasma membrane [23,24]. Isolating the lipid rafts from toxin-exposed cells, therefore, appeared as an efficient way to enrich for proteins with key functions in regulating the observed cytoskeletal reorganization and disruption of cell-cell interaction that occur in cells exposed to PP-inhibitory toxins.…”
Section: Introductionmentioning
confidence: 99%